Identification of excretory secretory (ES) liquid antigen protein Fasciola gigantica with polyethilene glycol (PEG) separation - Yendri Junaidi; Ima Malawati; Made Sriasih (Indonesian Journal of Biotechnology, 2016)
Fasciola gigantica diagnosis usually performed by detection of worm eggs presence in the feces,but this conventional method has many disadvantages. Early diagnosis (early detection) cannot be performed in conventional methods because the worms in the host's body began to lay eggs at the age of 8–12 weeks of patency. The current detection method that is based on antibodyantigen reactions using excreted/secreted (ES) liquid by adult F. gigantica, is believed to be used for the early detection of fasciolosis. This study aimed to characterize the antigenic components of F. gigantica extretory/secretory products that could be used as a vaccine candidate development for early fasciolosis diagnostics. ES products were separated by PEG4000 at various concentrations (8%, 16%, 24%), then precipitates (pellets) obtained were dialyzed and characterized using SDSPAGE and Western blotting. Results from SDSPAGE showed that there were 18 proteins bands with 7–70 kDa molecular weights. Western blotting on pellets derived from PEG separation at various concentrations affirmed that the proteins of 50, 25 and 20 kDa were antigenic at 8% PEG concentration, the 25 kDa and 50 kDa were antigenic at 16% PEG concentrations and the 25 kDa was antigenic at 25% PEG concentration